Association of Parental Height With Offspring Stunting in 14 Low- and Middle-Income Countries - Wu, Han; Ma, Chuanwei; Yang, Liu; Xi, Bo (Frontiers in Nutrition, 2021)
Background: Maternal height has been confirmed to be associated with offspring stunting in low- and middle-income countries (LMICs), but only limited studies have examined the paternal-offspring association, and few studies have examined the joint effect of maternal and paternal height on stunting. Objective: To investigate the association between parental height and stunting of children aged under-five in LMICs. Methods: We obtained data from the Demographic and Health Surveys conducted in 14 LMICs during 2006-2016. The association between maternal and paternal height and height-for-age z score (HAZ) of children aged under-five was analyzed using a linear regression model in consideration of complex survey design, and regression coefficients (β) with 95% confidence intervals (CIs) were reported. Then, the association between maternal and paternal height quintile and child stunting was analyzed using a modified Poisson regression approach with robust error variance in consideration of complex survey design with adjustment for covariates. The effect estimates were expressed as relative risks (RRs) with 95% CIs. Results: A total of 50,372 singleton children were included and the weighted prevalence of stunting was 34.5%. Both maternal height and paternal height were associated with child HAZ (β=0.047; 95% CI, 0.043, 0.050; and β=0.022; 95% CI, 0.018, 0.025, respectively). Compared with those who born to the tallest mothers and fathers, children from the shortest mothers and the shortest fathers had higher risks of stunting (adjusted RR = 1.89; 95% CI, 1.78, 2.01; adjusted RR = 1.56; 95% CI, 1.47, 1.65, respectively). The mother-offspring associations is substantively larger than the father-offspring associations for each corresponding height quintile. Children from the shortest parents had the highest risk of stunting compared with children from the tallest parents (adjusted RR = 3.23; 95% CI, 2.83, 3.68). Conclusions: Offspring born to short parents are at increased risk of stunting in LMICs, and this intergenerational effect is partly driven by maternal intrauterine influence. This suggests the importance of improving the nutritional status of children and adults in LMICs, especially female caregivers.